Repercussões dos fatores socioeconômicos, de estilo de vida e nutricionais no ganho ponderal excessivo no ciclo gravídico-puerperal - COSTA, Bárbara Miranda Ferreira (2010)
The excessive gestational weight gain can cause harmful consequences for both the mother and for the fetus. Nutritional, lifestyle, economic and social factors can affect the weight gain above recommendations. Objectives: To evaluate the nutritional (caloric intake, macro and micronutrients), lifestyle (smoking, physical activity, reproductive behavior) and economic (income) factors associated with the excessive weight gain in eutrophic pregnant women. Methods: This case-control study included 200 low-risk pregnant women in 2 public obstetric hospitals in Goiás, Brazil. The women that agreed to this study were divided in 2 groups: cases with excessive weight gain (> 16Kg) and controls within the recommended weight gain for eutrophic pregnant (11.50 < a < 16Kg), matched on age. The women were inquired about their food intake during the gestational period, by means of a quantitative and qualitative food-frequency questionnaire validated and adapted to the low income regional people. The women were inquired about their economic and lifestyle conditions, too. The software for statistical analyze were the SPSS version 17.0. Were used the folowing tests: Kolmogorov-Smirnov, Fisher, Student´s t, chi-square (x²), odds ratio (CI 95%), Mann-Whitney, Spearman´s correlation coefficient and multivariate linear regression. Results: The median age was 25.00 (22.00-29.00) years-old for cases and 24.00 (22.00-28.00) years-old for controls (p=0.52). The median per capita income was R$ 303.75 (225.60-500.00) for cases and R$ 333.33 (175.00-480.00) for controls (p=0.41). The median education level was 10.50 (9.00-12.00) years for cases and 11.00 (9.00-12.00) years for controls (p=0.77). There was 13.00 (13%) smokers among cases and 8.00 (8%) among controls (p=0.25). The frequency of regular physical activity was 28.00 (28%) pregnant women among cases and 31.00 (31%) among controls (p=0.65). About the reproductive behavior, there were no differences between groups for the parity (p=0.45) and abortion (p=0.90). The birth interval was 27.00 (0.00-60.75) months in cases and 22.50 (0.00-47.75) in controls (p=0.34). The following variables showed in the univariate analysis a significant correlation coefficient (ρ) to the weight gain: calories = 0.15 (p=0.04), protein = 0.16 (p=0.03), total cholesterol = 0.21 (p<0.01), retinol = 0.21 (p<0.01), iron = 0.18 (p=0.01), zinc = 0.15 (p=0.04), selenium = 0.19 (p<0.01) and phosphorus = 0.16 (p=0.03). The median of the satured fat intake was 36.57 grams (23.37 51.06) in the case group and 28.21 grams (19.92 41.90) in the control group (p=0.04). In the multivariate analysis the protein intake was the only independente variable associated with excessive pregnant weight gain. Conclusion: The factors associated with the excessive weight gain in the group of cases were total caloric intake, proteins, satured fat, cholesterol, retinol, iron, zinc, selenium and phosphorus, and in special, the protein intake. Lifestyle and economic factors didn t affect weight gain.